PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANGGULANGI PERGAULAN BEBAS DI SMK NEGERI 1 SARIREJO LAMONGAN - Ahmad Miftahul Maarif; Ahsantudhonni Ahsantudhonni (MIYAH : Jurnal Studi Islam, 2022)
Abstract: This research was motivated by the importance of the role of islamic education teachers as aducator in tackling promiscuity. Moreover, promiscuity is now increasingly widespread. Also, the development of adolescents who are in early maturity tend to be easily influenced on the negative things. Thus, islamic education teachers have a very important role in tackling promiscuity. In this case the researcher discussed related about the role of Islamic Education Teachers in tackling promiscuity, especially in SMK Negeri 1 Sarirejo. This study focused on: (1) How is the role of Islamic education teachers as educators in tackling promiscuity in SMK Negeri 1 Sarirejo? (2) What are the Supporting and Inhibiting Factors in tackling promiscuity in SMK Negeri 1 Sarirejo? This thesis was based on field data using qualitative research. Data were collected using observation data collection, interviews, and documentation. Meanwhile, in the analysis, researchers used data reduction, data presentation and conclusion. This study also uses data validity checking of which extend participation, persistence observation, and triangulation of sources, methods and inspection peers. The results of this study indicated that the role of PAI teachers as educators in tackling promiscuity is good. First, the role of Islamic Education Teachers as educators in tackling promiscuity is to inserting material of sex education in the subjects of Islamic Religious Education, provide reinforcement in religious education, familiarize good attitude, give religious activities and familiarize discipline. Second, the supporting factors in tackling promiscuity in SMK Negeri 1 Sarirejo are parental attention, the existence of religious activities and habituation, and also economic conditions. While the inhibiting factors in guiding the sex education are the environment, gadgets, lack of parental attention, and truancy of student.Keyword: The role of Islamic Education Teachers, Promiscuity.